Secured Transparent Computerized Voting System performance measurements - Elbarbary, Enas; Abdelhady, Ghada; Elbehiery, Hussam; Zekry, Abdelhalim (International Journal of Engineering and Technology, 2015)
In this paper, a multipurpose Secured Transparent Computerized Voting System (STCVS) is proposed. STCVS introduces an improvement methodology to the regular election systems. It could handle electronic ballots with multiple scopes at the same time, e.g., presidential, parliamentary, local, amongst others. STCVS’s design warrants well-secured identification and authentication processes for the voter via using voter’s digital signatures, certificates. Also, it guarantees voting data protection via encryption. Tallying of the voting counts is achieved automatically; candidates recorded percentages are displayed as charts for the supervision trusted parties. STCVS eliminates counting errors, voting duplication, and vote attack raised in paper-based elections systems. Voting transparency is achieved through the election process steps to assure voting credibility. This is confirmed by a feedback e-mail that the voter receives after finalizing the voting process. In addition, the proposed system saves the huge budget required for authentication devices, Electronic Voting Machines (EVM) that consist similar voting systems. To evaluate the robustness and reliability of the proposed system, performance measurements were achieved by applying the Avalanche Effect (AE) tests. Results of these measurements show the degree of security and the performance of the proposed system.